CHALLENGES AND PROSPECTS IN SUSTAINING FOUNDATION EDUCATION IN NIGERIA - Inuwa, Awwalu Muhammad (Sokoto Educational Review, 2020)
This paper is on challenges and prospects in sustaining foundation education in Nigeria. The present chorus of disapproval of Nigerians on education quality, low productivity from school leavers and graduates and a total set-back of the entire school and schooling products and processes is at the peak. As a result, this paper viewed the general problems of Nigerian education right from the foundational level, the micro stage of plan, implementation and provision. To this background the paper stresses on the importance of foundation education, presents the meaning and outlined, logical steps to fortify the pledge of the universalization of foundation education in Nigeria. A highlight on early foundation of education was given, challenges facing efficient foundation education were stated and proposed strategies to re-strength and build up strong foundation education was provided. Among the prospect for the future foundation education is implementing a properly planed foundation education that will bridge the gap of inequality among school children, improve on contents and structures of teaching and learning to promote self-reliance kind of education, with the vision of vocationalizing educational contents. Therefore a progressive foundation education should embrace social change and trot to be stagnant in nature.